2022
DOI: 10.1021/acsestwater.2c00339
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Surface Wettability to Alleviate Membrane Scaling in Photothermal Membrane Distillation

Abstract: To address the growing demand for fresh water with a smaller carbon footprint, photothermal membrane distillation (PMD) has been proposed by combining membrane distillation with solar irradiation. Due to its low level of energy consumption and portability, PMD is becoming increasingly attractive for water production in off-grid areas. However, it still suffers from several challenges, including membrane scaling. To address this issue, we developed photothermal membranes with different wettabilities. #PCNT-2 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The flux dropped to 0 when the volume concentration factor reached 1.30. The faster scaling could be explained by the surface carboxyl functional groups of the TFC Janus membrane (Figure a); for that, calcium was enriched at the surface through calcium bridging, which facilitated CaSO 4 scaling through surface nucleation and growth. , However, until the end of the experiment, the distillate conductivity remained unchanged, indicating that no wetting occurred. According to the SEM observation at the end of the experiment, the surface of both membranes was covered with acicular gypsum crystals (Figure S12a,b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The flux dropped to 0 when the volume concentration factor reached 1.30. The faster scaling could be explained by the surface carboxyl functional groups of the TFC Janus membrane (Figure a); for that, calcium was enriched at the surface through calcium bridging, which facilitated CaSO 4 scaling through surface nucleation and growth. , However, until the end of the experiment, the distillate conductivity remained unchanged, indicating that no wetting occurred. According to the SEM observation at the end of the experiment, the surface of both membranes was covered with acicular gypsum crystals (Figure S12a,b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, thermoplasmonic effects have been successfully exploited for photothermal cancer therapy [80,[83][84][85][86][87][88], photothermal actuators [89], nanofurnaces for heterogeneous catalysis [90], solar-driven hydrogen generation [91][92][93], and solar-driven water evaporation [94][95][96][97][98][99][100][101]. Interestingly, the embodiment of thermoplasmonics in membranes has gained great attention demonstrating the potential to mitigate the water-energy nexus in MD by reducing the anthropic energy input required to heat-up the feed and increasing the productivity of the desalination operation by overcoming the TP [102][103][104][105][106][107][108][109].…”
Section: Statusmentioning
confidence: 99%
“…[76] Some researchers reported that Janus membranes with a hydrophilic surface toward the feed side exhibited superior anti-scaling properties compared with hydrophobic ones because of the promoted salt solubility on the membrane surface. [156,86] Therefore, the effects of surface wettability on membrane scaling and fouling during photothermal MD need further investigation. Beyond surface wettability, an ideal MD membrane is supposed to facilitate mass transfer while hindering heat transfer.…”
Section: Photothermal Membrane Distillationmentioning
confidence: 99%